Relaxation Progressive Muscle Program on Exercise Behavior and Clinical Outcomes among Hypertension Patients - Rian Adi Pamungkas; Wahyu Kirana; Florensa Florensa (International Journal of Public Health Science (IJPHS), 2016)
The objective of this study was to examine the effect of relaxation progressive muscle program on exercise behavior and clinical outcomes among Patients with Hypertension in a Community Setting, in Indonesia. A quasi-experimental, two group, pre-test and post-test design was used in this study. The experimental group received relaxation progressive muscle program, whereas the control group did not receive the program. 30 subjects in the experimental group and 30 subjects in the control group completed the program, respectively. The results of this study indicated that significantly differences on exercise behavior (p = 0.000), blood pressure level (p = 0.000) and cholesterol total level (p = 0.000) between the experimental group and control group. The relaxation progressive muscle program was absolutely effective to improve the exercise behavior, blood pressure level and cholesterol total level among patients with hypertension. Further studies should be recognized by using larger groups over a longer time frame and Health care providers also should focus in promoting this program among patients with hypertension.